Micro-LEGO for MEMS - Seok Kim (Micromachines, 2019)
The recently developed transfer printing-based microassembly called micro-LEGO has been exploited to enable microelectromechanical systems (MEMS) applications which are difficult to achieve using conventional microfabrication. Micro-LEGO involves transfer printing and thermal processing of prefabricated micro/nanoscale materials to assemble structures and devices in a 3D manner without requiring any wet or vacuum processes. Therefore, it complements existing microfabrication and other micro-assembly methods. In this paper, the process components of micro-LEGO, including transfer printing with polymer stamps, material preparation and joining, are summarized. Moreover, recent progress of micro-LEGO within MEMS applications are reviewed by investigating several example devices which are partially or fully assembled via micro-LEGO.